RNA-seq analysis reveals differences in transcript abundance between cultured and sand fly-derived Leishmania infantum promastigotes. Issue 4 (August 2018) - Alcolea, Pedro J.; Alonso, Ana; Baugh, Loren; Paisie, Carolyn; Ramasamy, Gowthaman; Sekar, Aarthi; Sur, Aakash; Jiménez, Maribel; Molina, Ricardo; Larraga, Vicente; Myler, Peter J.
Abstract: Leishmania infantum is responsible for human and canine leishmaniasis in the Mediterranean basin, where the major vector is Phlebotomus perniciosus . Because isolation of sufficient parasites from the sand fly gut is technically challenging, axenic cultivation of promastigotes is routinely used to obtain material for biochemical and genetic analyses. Here, we report the use of Spliced Leader RNA-seq (SL-seq) to compare transcript abundance in cultured promastigotes and those obtained from the whole midgut of the sand fly 5 days after infection. SL-seq allows for amplification of RNA from the parasite avoiding contamination with RNA from the gut of the insect. The study has been performed by means of a single technical replicate comparing pools of samples obtained from sand fly-derived (sfPro) and axenic culture promastigotes (acPro). Although there was a moderate correlation (R 2  = 0.83) in gene expression, 793 genes showed significantly different (≥2-fold, p  <0.05) mRNA levels in sand fly-derived promastigotes and in culture, of which 31 were up-regulated ≥8-fold ( p  < 10 −8 in most cases). These included several genes that are typically up-regulated during metacyclogenesis, suggesting that sand fly-derived promastigotes contain a substantial number of metacyclics, and/or that their differentiation status as metacyclics is more advanced in these populations. Infection experiments and studies evaluating the proportion of metacyclic promastigotes in culture and within the sand fly gut, previously reported by us, support the last hypothesis. Graphical abstract: Unlabelled Image Highlights: SL-RNA-seq of L. infantum sfPro and acPro revealed highcorrelation (0.83). A total of 31 genes showed >8-fold up-regulation in sfPro vs. acPro, most involved in metacyclogenesis.